Challenges in Health Services Trade: Philippine Case - Maria Cherry Lyn S. Rodolfo; Jovi Dacanay (Philippine Institute for Development Studies (PIDS), 2005)
There is a growing emphasis on the role of trade in health services (telehealth, health tourism and retirement, investments and deployment of medical professionals) in easing fiscal constraints, generating jobs and income, improving infrastructure and financing, and upgrading the capacities of health professionals. This paper seeks to identify the opportunities, barriers, and risks for the Philippines in participating in global trade in health services. It examines the countrys capabilities in engaging in trade and identifies strategic directions that the Philippines can pursue. It also presents the different market niches that can be tapped relative to the opportunities, namely: the aging populations of the Organisation for Economic Co-operation and Development (OECD) nations; the shortage of medical professionals in those countries; the long waiting lines in hospital facilities; the Health Insurance Portability and Accountability Act of the United States; and the poor healthcare systems in other countries. It also addresses the weaknesses in the supply capabilities of the country–the lack of a policy framework to develop the healthcare services sector in a globalized environment, the lack of human resources planning, and the lack of alignment in the initiatives of the government and private sector.
Keywords: 330; services sector; health care; retirement; health services; health tourism; health professionals; Gesundheitswesen; Internationaler Wettbewerb; Gesundheitsfinanzierung; Gesundheitsversorgung; Philippinen